XML based architectures for documents comparison, categorisation, and scrutinisation. (15th December 2010) - Prajapati, Harshad B.; Dabhi, Vipul K.
Three document processing operations: comparison, categorisation, and scrutinisation are fundamental problems in any organisation that bases its business operations on electronic documents. We propose XML based architectures for documents comparison, categorisation, and scrutinisation. We also discuss all the components that are used in constructing these architectures. Moreover, we implement these proposed architectures to validate the application of XML technology in document processing operations. We found motivating results from these three architectures for selected applications. Our proposed architectures have potential for solving problems related to automated resume comparison system, automated matrimonial match-maker system, automated tender selection, automated resume scrutinisation system, and so on.